Enhancing digital literacy through gamification-based project learning in social studies for digital natives - Anggraini, Diana Noor; Holilah, Mina; Sopianingsih, Pitria; Listiawati, Susi (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2024)
Digital natives grew up with the help of digital technology so they have a different learning style from other generations. Many educators face new challenges and have to solve problems related to learning adaptation New learning models and educational trends, reinforced by the use of information and communication technology, create a method for using new methods for active learning. Developing gamification through project learning in social studies learning is one thing that can be done. This research aims to see the implementation of gamification-based project learning in social studies learning. The research method used is through research and development and data collection methods through group discussions, observation and validating questionnaires The results of this research show that: First, the Gamification-Based Project Learning Model has a syntax that combines the main basic principles of Project learning and the principles of gamification learning, including determining learning objectives and game ideas, determining the big idea of the game, creating game scenarios, creating games through applications, produces products in the form of games that can be used in social studies learning.